Prevalence and abundance of coral disease in Aceh Besar regency Aceh, Indonesia - Maria Ulfah; Iqbal Nindo Turnip; Chitra Octavina; Irma Dewiyanti; Syahrul Purnawan (Depik, 2022)
The aims of this research was to knew the prevalence, abundance and types of coral diseases detected in Peukan Bada Aceh Besar Regency. Method used in this research was a 20x2m belt transect with 3 replicates. Results show that the prevalence value was between 27,94% 58,25%. The value was quite higher if compared with other prevalence on some place in indonesia. Average value of coral disease abundance in this research was 0,23 ind/m2. There was 13 types of coral disease found during sampling, including Fish Bite, Drupella Predation, Acanthaster planci Predation, White Syndrome, Ulcerative White Spot, Focal Bleaching, Non-Focal Bleaching, Invertebrate Galls, Sponge Overgrowth, Cyanobacteria, Pigmentation Response, Sedimentation Damage, Algae Overgrowth. The most infected coral genus was Acropora with branching growth form.Keywords:AbundanceConditionCoral diseasePrevalence